Revolutionary Changes in the University of the Information Society: Cultural Strategies for Equal Opportunities - Kolinko, Maryna; Kravchenko, Alla (Skhid, 2026)
The article provides a socio-philosophical analysis of the transformation of the university as an open scientific and educational space in the context of liquid modernity and digitalization. It is substantiated that contemporary changes represent not merely a crisis of the classical Humboldtian model, but its historical transformation into forms of networked and multidisciplinary knowledge organization. The author proves that the digitalization of education takes on the features of an epistemological and cultural-communicative revolution, which fundamentally alters the culture of cognition, the roles of teachers and students, and the very ontology of the university space. Particular attention is paid to the transformation of the human lifeworld (Lebenswelt): the study analyzes how digitalization reshapes the structures of experience, communication, and meaning-making, creating a hybrid educational reality. The ambivalent nature of these changes is revealed: from new opportunities for democratization and inclusion (based on the experience of leading world universities) to the risks of "techno-systemic colonization," the deepening digital divide, and the instrumentalization of knowledge through efficiency metrics. The concept of academic freedom is reimagined as a dynamic balance between autonomy and responsibility. The article concludes with the necessity of forming new educational strategies capable of ensuring the existential integrity of the individual in a situation of ontological instability within the information society.